Stability of Reactive Iron‐Bound Organic Carbon During Sulfidization of Iron Oxides: Insights From Methane‐Seep Sediments - Yu Hu; Kai Li; Johan C. Faust; Jörn Peckmann; Dong Zhang; Linying Chen; Qianyong Liang; Duofu Chen; Dong Feng (Geophysical Research Letters)
Abstract The association of organic carbon (OC) to reactive iron oxides (FeR), forming OC‐FeR complexes, represents a significant OC sink in marine sediments. However, the impact of diagenetic processes, such as sulfate reduction and iron sulfide formation, on the stability of OC‐FeR in marine sediments remains poorly understood. Here, we compare sulfidic sediments from three cores taken at methane seeps with a non‐sulfidic sediment record from a nearby site. Our results show that an overall 6.3% decrease in OC‐FeR is associated with a 42% reduction in FeR during the transformation from iron oxides to iron sulfides, suggesting that OC‐FeR is resistant to sulfidization. We observed highly 13C‐depleted OC‐FeR in the sulfidic sediments, likely due to the interaction between OC and FeR during anaerobic oxidation of methane. Our findings highlight the stability of OC‐FeR in natural sulfidic sediments, offering new insights into the role of OC‐FeR in continental margin sediments.